Dampak Teknologi Terhadap Praktik Akuntansi - Lumbanbatu, Maristella J.; Marpaung, Astrida N. (Cattleya Darmaya Fortuna, 2024)
Rapid technological advancement brings about major changes to the accounting industry. Because of these changes, accountants must stay up to date on advancements and increase their level of expertise. In the past, the evolution of accounting has been categorized into three distinct eras: the agricultural, industrial, and current information eras. Information technology (IT) will have a greater impact on the accounting industry the more sophisticated it becomes. The audit process is impacted by the advancement of computer-based AIS in financial report production. Although it initially caused concern for the accounting profession, the rise of IT ultimately opened up new opportunities for it. The new opportunities that can be achieved include computer-based information system audits, computer-based information system consultants and web trust audits. Advances in IT brought significant changes to the development of accounting and also brought many benefits for both employees and companies. Web trust audits, computer-based information system consultants, and computer-based information system audits are some of the new prospects that can be realized. The evolution of accounting saw substantial changes as a result of IT advancements, which also had numerous positive effects on businesses and personnel.